Religiosity as a Moderator of Self-Efficacy and Social Support in Predicting Traumatic Stress Among Combat Soldiers - Israel-Cohen, Yael (Journal of religion and health, 2016)
Based on a sample of 54 Israeli soldiers (51 % non-religious, 49 % religious) surveyed upon their return from combat, this study investigates the moderating role of religiosity as a factor that may strengthen cognitive processing tied to the belief in oneself to persevere (i.e., self-efficacy) after trauma and/or as a factor tied to enhanced external social support that religious individuals in particular may benefit from by their involvement in a religious community. Findings revealed (1) social support was tied to greater resilience within the general sample; (2) religious soldiers were less susceptible to traumatic stress than non-religious soldiers; and (3) religiosity moderated the relationship between self-efficacy and traumatic stress but not the relationship between social support and traumatic stress. Implications of findings are discussed.